2006
DOI: 10.2193/0084-0173(2006)164[1:eofpia]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Potentially Influencing a Desert Bighorn Sheep Population

Abstract: We studied a desert bighorn sheep (Ovis canadensis) population in the Mazatzal Mountains (primary study area) in central Arizona and population indices on reference areas between 1989 and 2003. We evaluated disease exposure and nutritional status of desert bighorn sheep, vegetation parameters, predator diets, and mountain lion (Puma concolor) harvest and abundance (1999)(2000)(2001)(2002)(2003) and mountain lion predation (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) as factors potentially affecting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
1
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 148 publications
(354 reference statements)
2
30
1
18
Order By: Relevance
“…Because seasonal precipitation dictates water availability and plant productivity in desert ecosystems (Reynolds et al ), even small changes in precipitation amount or patterns can have substantial effects on populations of desert wildlife and the habitat features on which they depend (Brown et al ). Desert‐dwelling herbivores, for example, will respond to shifts in rainfall and related changes in plant biomass to meet their forage and water requirements (Marshal et al , McKinney et al ). For free‐ranging ungulates, balancing water and nutrient requirements with predation risk is an important determinant of habitat use (Festa‐Bianchet , Parker et al ), particularly in dynamic desert environments (Berger 1983, Redfern et al , Marshal et al ).…”
mentioning
confidence: 99%
“…Because seasonal precipitation dictates water availability and plant productivity in desert ecosystems (Reynolds et al ), even small changes in precipitation amount or patterns can have substantial effects on populations of desert wildlife and the habitat features on which they depend (Brown et al ). Desert‐dwelling herbivores, for example, will respond to shifts in rainfall and related changes in plant biomass to meet their forage and water requirements (Marshal et al , McKinney et al ). For free‐ranging ungulates, balancing water and nutrient requirements with predation risk is an important determinant of habitat use (Festa‐Bianchet , Parker et al ), particularly in dynamic desert environments (Berger 1983, Redfern et al , Marshal et al ).…”
mentioning
confidence: 99%
“…These results suggested that fecal DAPA was able to track changes in energy content in mule deer diets, from high-energy fruits in summer to high-energy annual forbs in winter. Changes in fecal DAPA that follow seasonal patterns in plant phenology and precipitation have been reported in mule deer and bighorn sheep field studies (Leslie et al, 1989;Kucera, 1997;McKinney et al, 2006).…”
Section: Results-recruitment and Precipitation Data-mentioning
confidence: 69%
“…However, mule deer consume large amounts of fruits during summer in the TBWA (McCulloch, 1973), and the low levels of FN observed in summer 2005 in relation to summer 2004 may be related to decreased availability of fruits after the fire. Mule deer FN values in the TBWA ranged between 2.3 and 3.9%, whereas values between 1.1 and 2.3% were reported for desert bighorn sheep in the vicinity (McKinney et al, 2006). A study with penned white-tailed deer fed low protein and low energy diets had 1.7% of FN, and white-tailed deer under medium protein and medium energy had 2.3% FN (Brown et al, 1995).…”
Section: Results-recruitment and Precipitation Data-mentioning
confidence: 89%
See 2 more Smart Citations